2011
DOI: 10.4081/jlimnol.2011.305
|View full text |Cite
|
Sign up to set email alerts
|

Vitality of aquatic plants and microbial activity of sediment in an oligotrophic lake (Lake Bohinj, Slovenia)

Abstract: The vitality of eight macrophyte species and the microbial activity of sediment in an oligotrophic lake (Lake Bohinj, Slovenia) were studied via the terminal electron transport system (ETS) activity of mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…Further the diagenesis of organic matter in sediments takes place via oxic and anoxic microbial activities with the consumption of electron acceptors such as oxygen causing an oxygen deficient zone. Under such anoxic conditions bacterial cells (facultative anaerobes) capable of using NO 3 1-, SO 4 2-and CO 2 as terminal electron acceptor to decompose the organic matter (Steenberg et al 1993 become more active causing a high electron transport system (ETS) activity in the sediments (Germ and Simčič, 2011). Methanogens produce methane (CH 4 ) from CO 2 by reducing it with H 2 .…”
Section: Aquatic Plant-microbe Interaction and Its Role In Freshwatermentioning
confidence: 99%
“…Further the diagenesis of organic matter in sediments takes place via oxic and anoxic microbial activities with the consumption of electron acceptors such as oxygen causing an oxygen deficient zone. Under such anoxic conditions bacterial cells (facultative anaerobes) capable of using NO 3 1-, SO 4 2-and CO 2 as terminal electron acceptor to decompose the organic matter (Steenberg et al 1993 become more active causing a high electron transport system (ETS) activity in the sediments (Germ and Simčič, 2011). Methanogens produce methane (CH 4 ) from CO 2 by reducing it with H 2 .…”
Section: Aquatic Plant-microbe Interaction and Its Role In Freshwatermentioning
confidence: 99%
“…Species richness of the natural ponds was considerably lower than that in natural oligotrophic to mesotrophic lakes in high-mountain systems across Europe, where a much broader spectrum of macrophyte species is known, including several Charophytes and more vascular plants of the genera Potamogeton, Isoëtes, Batrachium, and others [10,12,33,34]. Macrophyte species richness in artificial Tatra ponds is comparable or slightly lower than the richness of pond ecosystems across Europe [35,36].…”
Section: Species Richness and Composition And Their Relation To Envirmentioning
confidence: 99%
“…Even though several regional studies from particular mountain lakes have been published recently [10][11][12][13], there is still much that remains open for study.…”
Section: Introductionmentioning
confidence: 99%
“…* Samples connected by ( ) are not significantly different at P < 0.008. Previous studies identified that macrophytes can affect sediment chemistry, as well as stimulate microbial processes in sediment (Germ and Simčič, 2011). This study showed that there were slight differences of TP, OP, IP, TN, OM concentrations in the sediment among all four systems, neither the significant effect of the macrophytes (P > 0.05).…”
Section: Discussionmentioning
confidence: 57%